Gerakan Sweri Stunting (Gesit) Melalui Pelatihan dan Pendampingan Kader di Desa Latdalam Kabupaten Kepulauan Tanimbar - Salakory, Jacomina A.; Wijayanti, Hesty; Fajni, Deby Nur (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Community Service Activity (PKM) "SWERI Stunting Movement (GESIT)" in Latdalam Village aims to overcome the problem of stunting which reached 26.1% in 2022, exceeding the threshold set by WHO. This problem is exacerbated by the low skills of posyandu cadres in anthropometric measurements and interpretation of results, which hinders monitoring of children's nutritional status. To overcome this, the method used in this activity is training and mentoring for posyandu cadres designed to improve knowledge and skills in taking measurements and providing education on balanced nutrition. The results of this activity showed a significant increase in cadre skills, where all skill indicators reached 100% after training. Thus, GESIT activities are expected to contribute to reducing stunting rates and improving public health in Latdalam Village as a whole.